Transformasi Identitas dan Spiritual Pasca Kerasukan: Analisis Naratif atas Perikop Markus 5:1-20 - Gebrile Mikael Mareska Udu (Fakultas Teologi, Universitas Sanata Dharma, 2026)
This article analyzes the story of Jesus casting out evil spirits from a possessed person in the Gerasene region using the narrative interpretation method. Researcher chose to use this method because it can discover the meaning of narrative. This method helps researcher to analyze the theological meaning hidden behind the structure of the story especially on the dynamics of the plot, characters, literal meaning, setting and the symbol used by the evangelist in Mark 5:1-20. The results of the study reveal a transformative experience of the possessed in terms of change in identity and spirituality after meeting with Jesus. He who was initially shackled by the power of evil spirits, living in the tombs, and was excluded from society, was restored by Jesus to become a civilized person, well-dressed, sane or a new man. This transformative experience aims to emphasize Jesus’ authority as the son of God before humans and evil spirits (legions). This article, in turn, serves as an example that the story of Jesus’ exorcism does not merely describe Jesus’ victory or the power of darkness, but rather a reflection for readers to discover a new identity before God and willingly to be witnesses of faith in common life.AbstrakArtikel ini menganalisis kisah Yesus yang mengusir roh jahat dari pribadi yang kerasukan di daerah Gerasa dengan menggunakan metode tafsir naratif. Metode ini membantu peneliti untuk menganalisis dinamika alur, tokoh, latar serta pengalaman transformatif yang dialami oleh pribadi yang kerasukan tatkala berjumpa dengan Yesus. Keputusan peneliti untuk menggunakan metode tersebut karena mampu menemukan makna teologis yang tersembunyi di balik struktur cerita, karakter tokoh, makna literer serta simbol yang digunakan penginjil dalam teks Markus 5:1-20. Hasil penelitian mengungkapkan bahwa adanya perubahan identitas dan spiritual yang dialami oleh si kerasukan pasca berjumpa dengan Yesus. Dia yang mulanya dibelenggu oleh kuasa roh jahat, hidup berkeliaran di kuburan, dan disingkirkan dari lingkungan masyarakat boleh dipulihkan oleh Yesus menjadi pribadi yang beradab atau singkatnya menjadi manusia baru. Pengalaman transformatif ini hendak menegaskan otoritas Yesus sebagai anak Allah di hadapan manusia dan roh jahat (legion). Artikel ini pada giliranya menjadi contoh bahwa kisah eksorsisme yang dilakukan Yesus tidak semata-mata menggambarkan kemenangan Yesus atau kuasa gelap tetapi cerminan bagi pembaca untuk menemukan identitas baru di hadapan Tuhan dan rela menjadi saksi iman dalam kehidupan bersama.